Modeling the US-China Trade Conflict: A Utility Theory Approach - Yuhan Zhang; Cheng Chang (Journal of Applied Mathematics and Computation, 2021)
This paper models the US-China trade conflict initiated in 2018 and attempts to analyze the (optimal) strategic choices of the United States and China. In contrast to the existing literature on the topic, we employ the expected utility theory and examine the conflict mathematically. In both perfect information and incomplete information games, we show that expected net gains diminish as the utility of winning increases because of the costs incurred during the struggle. We find that the best response function exists for China but not for the US during the conflict. The results of our models indicate that the less the US pressures China to change its existing trade practices, the higher the US expected net gains. China's best choice is to maintain the status quo, and any further aggression in its policy and behavior, such as artificially adjust exchange rates and slash imports from the US, will aggravate the situation. The theoretical framework designed in this paper can be also used to examine the bilateral technological frictions. – – This economics paper models the U.S.-China trade war and explains the strategic decision-making of both sides. Math-driven findings include (1) For the bilateral trade frictions which involve not only the balance of payments but also tech rivalry, the probability for the U.S. win is higher than China's. (2) In both perfect information and incomplete information games, the U.S. cannot find a strategy to achieve the optimal result (i.e. maximum expected net benefits). (3) In both above-mentioned games, China has the best response function to achieve its maximum expected net gains if it can maintain the status quo. (4) During the ongoing trade war, the more the U.S. pressures China through protectionist tariffs or other punitive measures, the less the U.S. expected net benefits. On the Chinese side, any aggression in its policies or practices, such as slash imports from the U.S. and artificially depreciate the renminbi, will reduce China's expected net utilities and the situation will be aggravated. (5) The theoretical framework and mathematical models designed in the article contribute to the existing scholarly literature on the U.S.-China trade war and the expected utility theory and can be applied to analyzing technological competition/financial flare-ups between the two economic powers.
Keywords: C00; F10; 330; US-China Trade War; Utility Theory Models; Perfect Information; Incomplete Information; Expected Net Gains